Unravelling the sponge diversity of the Tuscan Archipelago National Park (Tyrrhenian Sea, Italy) - Roveta, C.; Marrocco, T.; Calcinai, B.; Pulido Mantas, T.; Pica, D.; Valisano, L.; Puce, S. (The European Zoological Journal, 2022)
Porifera are considered key components of benthic communities, being typical inhabitants of both shallow and deep waters, from the mesolittoral to the bathyal zone. Although sponges are one of the most common organisms in Western Mediterranean ecosystems, in many areas the knowledge on this taxon is still very limited. In the current study, we aim to analyse and compare the sponge communities characterising the hard bottoms of two islands, Montecristo and Giglio, belonging to the Tuscan Archipelago National Park (TANP, Italy), in relation to a bathymetric gradient. A total of 340 samples were collected, 13 orders and 48 species (46 Demospongiae and 2 Calcarea) identified, with Chondrosia reniformis representing the most recorded species, being found at all sites at almost all depths. Depth was the only significant factor in the observed pattern, while the sponge community is shared between the two Islands. In addition, our data were analysed together with data available in the literature on sponges of the Tuscan Archipelago, to assess the sampling effort. Among all the Islands of the Archipelago, Giglio and Montecristo showed the higher mean species diversity. Nonetheless, the sampling effort resulted not sufficient for each Island and future studies targeting Porifera are needed. Our work is the first summarising the sponge diversity of the entire Tuscan Archipelago, and one of the few focussing entirely on the sponge fauna. These results provide new important information on the area of the TANP, aimed to become a future Marine Protected Area, adding new records, and highlighting the high diversity of a poorly known area.